Artificial Intelligence Technologies in Banking Innovation Management from the Perspective of Economic Security (on the example of China Construction Bank) - Seungkyu Yoon, Seungkyu Yoon (Интеллект. Инновации. Инвестиции, 2025)
The relevance of the study is due to the increasing role of artificial intelligence (AI) in ensuring the economic security of the banking sector against the background of digital transformation and growing volatility of global financial markets. The analysis of the impact of AI-technologies on the value of financial organizations is of particular importance, which allows to identify optimal strategies for their implementation. The purpose of the study is to assess the effectiveness of AI solutions in bank management on the example of China Construction Bank and to determine their impact on the indicators of economic security and market value of the bank. The methodological framework includes a comprehensive quantitative and qualitative analysis of key performance indicators for the period 2016-2024, comparative assessment of four basic sectors: competitiveness, liquidity, management efficiency and additional indicators. The main results show that the systematic implementation of AI algorithms allowed the bank to significantly improve operational efficiency through real-time tracking of external environment changes, monitoring of financial indicators and forecasting of development scenarios. This ensured sustainable growth in the bank’s market value even in the face of pandemic and geopolitical instability. Scientific novelty consists in the confirmation of the hypothesis of positive correlation between the level of technological equipment of the bank and its value, as well as in the development of a methodology for assessing the effectiveness of AI solutions. The practical significance of the research consists in the possibility of using the obtained data to improve the economic risk management system in the banking sector. The results can be applied by other financial organizations in the development of digital transformation strategies. Areas for further research include studying the impact of different types of AI solutions on certain aspects of banking activities, as well as assessing the long-term effects of their implementation. It is recommended to expand the geography of the study to include other large banks.